Sanksi Pidana terhadap Perbuatan Pencemaran Lingkungan Hidup oleh Limbah Sablon dan Pencelupan di Kota Denpasar - I Made Della Dwi Angga Saputra; Anak Agung Sagung Laksmi Dewi; Luh Putu Suryani (Fakultas Hukum, Universitas Warmadewa, 2020)
Denpasar City is the center of government, population center, tourism center, trade center, economic activity and center for other activities so you can imagine how busy Denpasar City is in handling all aspects of people's increasingly complex life. An incident that looks easy but few people care about, one of which is waste, so many effects can be obtained from disposing of the residual use of fragrances and screen printing, which are often found, but without a clear response to allow the accumulation of waste. Even though the government has regulations and sanctions related to these problems, they are often ignored by owners or entrepreneurs engaged in screen printing. Environmental pollution, which has often occurred since a long time ago, is a community disease that is difficult to eliminate. The researcher has a problem formulation covering 1) How is the legal arrangement regarding criminal acts against environmental pollution by screen printing and dyeing waste in Denpasar City? 2) What are the criminal sanctions against the perpetrators of criminal acts of environmental pollution by screen printing and dyeing waste in Denpasar City? The research was carried out by reviewing books on law and not deviating from the problems studied and the current positive law as well as studies in the library, this research is often called normative research. The results of this study state that criminal sanctions against perpetrators of environmental pollution by screen printing and dyeing waste in Denpasar City are in the form of fines and imprisonment. The act of environmental pollution carried out by NHY by disposing of screen printing waste into the river has violated Article 58 paragraph (2) of the Regional Regulation on the City of Denpasar Number 1 of 2015.